Stable gene replacement in barley by targeted double-strand break induction - Watanabe, Koichi; Breier, Ulrike; Hensel, Götz; Kumlehn, Jochen; Schubert, Ingo; Reiss, Bernd (Journal of Experimental Botany, 2016)
Gene targeting is becoming an important tool for precision genome engineering in plants. During gene replacement, a variant of gene targeting, transformed DNA integrates into the genome by homologous recombination (HR) to replace resident sequences. We have analysed gene targeting in barley (Hordeum vulgare) using a model system based on double-strand break (DSB) induction by the meganuclease I-SceI and a transgenic, artificial target locus. In the plants we obtained, the donor construct was inserted at the target locus by homology-directed DNA integration in at least two transformants obtained in a single experiment and was stably inherited as a single Mendelian trait. Both events were produced by one-sided integration. Our data suggest that gene replacement can be achieved in barley with a frequency suitable for routine application. The use of a codon-optimized nuclease and co-transfer of the nuclease gene together with the donor construct are probably the components important for efficient gene targeting. Such an approach, employing the recently developed synthetic nucleases/nickases that allow DSB induction at almost any sequence of a genome of interest, sets the stage for precision genome engineering as a routine tool even for important crops such as barley.
Keywords: Transformation, Genetic; transformace genetická; typy dědičnosti; Hordeum; DNA Breaks, Double-Stranded; Inheritance Patterns; dvouřetězcové zlomy DNA; genový targeting; genetické lokusy; geneticky modifikované rostliny; reprodukovatelnost výsledků; rostlinné geny; Genes, Plant; Gene Targeting; Plants, Genetically Modified; Reproducibility of Results; modely genetické; Real-Time Polymerase Chain Reaction; ječmen (rod); Models, Genetic; Genetic Loci; kvantitativní polymerázová řetězová reakce